Effects of nitrogen fertilization and bioenergy crop type on spatial distributions of extracellular hydrolases associated with nitrogen and phosphorus acquisition - Jianwei Li; Xuehan Wang; Siyang Jian; Lahiru Gamage; Dafeng Hui; Philip A. Fay (Scientific Reports)
Abstract Extracellular hydrolases associated with nitrogen (N) and phosphorus (P) acquisition are important for soil nutrient cycling. The spatiotemporal patterns of N- and P-hydrolases were rarely studied under N fertilization. It is also unclear whether the N fertilization effects likely vary among different crop species. This study employed a spatially explicit design and clustered soil sampling strategy (288 samples at 0–15 cm) in a fertilization experiment with zero, low and high N input (NN, LN and HN: 0, 84, and 168 kg N ha− 1 yr− 1 urea, respectively) in switchgrass (SG: Panicum virgatum L.) and gamagrass (GG: Tripsacum dactyloides L.) croplands in Middle Tennessee. N-acquisition hydrolases such as leucine aminopeptidase (LAP), β-N-acetylglucosaminidase (NAG), their sum (N acq ), urease (UREA), and P-acquisition hydrolase acid phosphatase (AP) were quantified. Geostatistical analyses were applied to explore the effects of fertilization and plant type on spatiotemporal variations of N- and P-hydrolases. Results showed large plot-to-plot spatial variation and generally increased variation in soil hydrolyses with N fertilization in both croplands. NAG and N acq were significantly higher by 15–32% in GG than in SG soils. Relative to NN, HN significantly increased LAP by 54% in SG soils. LAP appeared to be highly responsive to N fertilization. Overall, this study suggested greater sensitivity and responsiveness of spatiotemporal dynamics to N fertilization in SG cropland. Future studies will examine whether a specific peptidase (i.e., LAP) may facilitate soil C and N sequestration under intensive fertilization in switchgrass soil.